2015
DOI: 10.1002/ajmg.a.37007
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal polysomnographic findings in infantile Pompe disease

Abstract: Infantile Pompe disease is a rare, metabolic disorder due to deficiency of the enzyme acid α-glucosidase that degrades lysosomal glycogen. The deficiency leads to multisystem dysfunction. Neuromuscular weakness due to metabolic myopathy is present, which predisposes children to sleep-disordered breathing. With the advent of enzyme replacement therapy (ERT), children are living longer, and there is a new natural history that is emerging. In a prior paper on our cohort of infantile Pompe disease patients, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…In children, OSA and hypoventilation are highly prevalent, and NIV sustainably corrects gas exchange. 28,29 In contrast to these two reports, we did not find central apneas to be of any relevance in adult patients. Our results confirm one previous study that applied NIV to eight patients with LOPD and advanced hypercapnic respiratory failure.…”
Section: Discussioncontrasting
confidence: 99%
“…In children, OSA and hypoventilation are highly prevalent, and NIV sustainably corrects gas exchange. 28,29 In contrast to these two reports, we did not find central apneas to be of any relevance in adult patients. Our results confirm one previous study that applied NIV to eight patients with LOPD and advanced hypercapnic respiratory failure.…”
Section: Discussioncontrasting
confidence: 99%
“…NIV improves gas exchange. Enzyme replacement therapy has a positive impact on ventilatory failure and survival [242,243,[270][271][272][273][274] (table e3.3.D).…”
Section: Acid Maltase Deficiencymentioning
confidence: 99%
“…We also demonstrated that speech therapies were not obviously effective in correcting hypernasality in children with IOPD [4]. A palatal lift prosthesis or surgical intervention may be necessary for these patients, but such management techniques may cause obstructive sleep apnea, which may occur with a high incidence in IOPD [22]. In contrast, CPAP training is safe and convenient for children with IOPD and should be initially considered for improving their hypernasality and speech intelligibility.…”
Section: Discussionmentioning
confidence: 90%